CONCENTRIC REDUPLICATIONS IN TURKEY TURKISH POETIC PROVERBS - Ahmet Çam (Uluslararası Türk Lehçe Araştırmaları Dergisi, 2018)
Proverbs are phrases that maintain their vitality in every period of Turkish language and literature. Many aspects such as reasons of formation, forms, historical and present uses, meanings and connotations, concepts in proverbs and motifs have been studied and continued to be analyzed by experts in language, folklore and literature. In the first part of this work, which consists of three parts, the formal and semantic features of proverbs are briefly explained based on the general proverb definitions. In the second part, the relation between the poetic and formal elements of the proverbs and the meaning of these elements are mentioned and the reduplications are especially addressed. In the third part, the definition of the concentric reduplications genre is given in the framework of the poetic proverb concept and the examples that are relevant to this genre are presented. The affinity of the proverbs which are embraced as concentric reduplications to the notion of the proverb and the frequency of usage in the dictionary are examined.